Synthesis of Chalcone Derivatives: Inducing Apoptosis of HepG2 Cells via Regulating Reactive Oxygen Species and Mitochondrial Pathway - Zhu, Hongtian; Tang, Lei; Zhang, Chenghong; Wei, Baochu; Yang, Pingrong; He, Dian; Zheng, Lifang; Zhang, Yang (Frontiers in Pharmacology, 2019)
Chalcone derivatives, as a hot research field, display a wide range of physiological activities and target a variety of biological receptors. Based on the parental structure of (E)-1,3-diphenyl-2-propene-1-one, 14 chalcone derivatives were designed and synthesized for the first time, and tested as the antitumor agents against four human cancer cell lines (A549, Hela, HepG2, and HL-60) and one normal cell line (WI-38). The most potent compound a14 displayed significant anti-hepatoma activity with IC50 of 38.33 μM and relatively weak cytotoxicity with IC50 of 121.29 μM in normal cells WI-38. In addition, compound a14 could effectively block the cell division of HepG2 cell lines in G2/M phase and robustly induced generation of ROS, and the application of the ROS scavenger N-acetylcysteine (NAC) could completely counteract the HepG2 cells death triggered by a14, which demonstrated that the generation of ROS induced by a14 was a main reason resulting in the apoptosis of HepG2 cells. Moreover, the mitochondrial membrane potential (MMP) of HepG2 cells treated with a14 was significantly decreased, which was closely related to ROS level. Furthermore, based on the Western blot experiment, cell apoptosis induced by a14 also involved the expression of Bcl-2 family and Caspase 3 protein. In summary, compound a14 could contribute the apoptosis of HepG2 cells via regulating ROS--mitochondrial pathway, which provide valuable hints for the discovery of novel anti-tumor drug candidates.